Ireland social, political, and religious - Beaumont, Gustave de, 1802-1866.; Taylor, W. C. (William Cooke), 1800-1849. (Cambridge, Mass. : Belknap Press of Harvard University Press, 2006)
Paralleling his friend Alexis de Tocqueville's visit to America, Gustave de Beaumont traveled through Ireland in the mid-1830s to observe its people and society. In Ireland, he chronicles the history of the Irish and offers up a national portrait on the eve of the Great Famine. Published to acclaim in France, Ireland remained in print there until 1914. The English edition, translated by William Cooke Taylor and published in 1839, was not reprinted. In a devastating critique of British policy in Ireland, Beaumont questioned why a government with such enlightened institutions tolerated such oppression. He was scathing in his depiction of the ruinous state of Ireland, noting the desperation of the Catholics, the misery of repeated famines, the unfair landlord system, and the faults of the aristocracy. It was not surprising the Irish were seen as loafers, drunks, and brutes when they had been reduced to living like beasts. Yet Beaumont held out hope that British liberal reforms could heal Ireland's wounds. This rediscovered masterpiece, in a single volume for the first time, reproduces the nineteenth-century Taylor translation and includes an introduction on Beaumont and his world. This volume also presents Beaumont's impassioned preface to the 1863 French edition in which he portrays the appalling effects of the Great Famine.
First epoch : from 1169 to 1535 -- Second epoch : from 1535 to 1690 -- Ch. I. Religious wars -- Third epoch : from 1688 to 1755 -- Ch. I. Legal persecution -- Ch. II. The penal laws -- Fourth epoch : from 1776 to 1829 -- Ch. I. Effects of American independence on Ireland -- Ch. II. The French revolution -- its effects in Ireland -- Ch. III. Catholic emancipation in 1829 -- Part I -- Ch. I. External appearance in Ireland : misery of its inhabitants -- Ch. II. A bad aristocracy is the primary cause of all the evils of Ireland : the faults of this aristocracy are, that it is English and Protestant -- Ch. III. Tithes -- Ch. IV. The north of Ireland -- Ch. V. Irish character -- Ch. VI. Illusions of the Irish aristocracy -- Part II (annexed to part I in the translation) -- Ch. VII. How Ireland tends to democracy -- Part III -- Ch. I. The three principle remedies that have been proposed for the evils of Ireland -- Ch. II. Remedies proposed by the author -- the civil, political, and religious privileges of the aristocracy must be abolished -- Ch. III. It would be an evil to substitute a Catholic aristocracy for the Protestant aristocracy -- Ch. IV. How the Irish aristocracy should be abolished -- Part IV -- Ch. I. What will England do? -- Ch. II. Relations of English parties to Ireland -- Ch. III. General survey of the state of Ireland -- Preface, 1863 : a report on the present state of Ireland (1862-1863).
Includes bibliographical references (pages xii-xiv) and index.
Translated from the French.
Print version record.
Master record variable field(s) change: 651
Keywords: Ireland -- Description and travel; Ireland -- Politics and government -- 1837-1901.; Ireland -- Economic conditions; Ireland -- Description and travel; Ireland -- Economic conditions; Ireland -- Politics and government -- 1837-1901.; HISTORY; HISTORY -- Europe -- General; Economic history; Politics and government; Travel; Ireland; 1837-1901; Electronic books